CO2 REMOVAL SYSTEM MODEL DESIGN WITH RATE BASED APPROACH AND INFLUENTIAL PARAMETERS SENSITIVITY ANALYSIS USING DESIGN OF EXPERIMENT METHOD - ANGGA SUWARDHANA (NIM : 22211005), ARI
Gas is becoming an increasingly important part of the global energy consumption that makes the exploitation of sour gas reservoir increasing rapidly. A major challenge to produce Sungai Kenawang Field as one of sour gas reservoir is reducing CO2 contents up to 5% mole. To reach that objective effectively, application of CO2 Removal System model with Rate Based approach as a tool to investigate field problem and future facility development becoming essential. CO2 Removal System model which appropriate with field facility utilized for sensitivity test and analysis that using Design of Experiment (DOE) method. With 3 stages of sensitivity levels each parameter: CO2 concentration (10%, 20%, 30%), MDEA concentration (2%, 4%, 5%), temperature (130oF, 106 oF, 81 oF) dan pressure (1106 psig, 1006 psig, 906 psig) the combination method that will be used is full factorial method which deliver 81 sensitivity data combination. Sensitivity test shows that the most influenced parameter is CO2 concentration of input stream which have directly proportional relationship with CO2 concentration output stream. On the other side, temperature and pressure of input stream tend to have not a huge effect to CO2 concentration of output stream. The optimum input stream configuration consist of 10% carbon dioxide concentration, 4% MDEA concentration with output stream temperature and presurre valued at 106,9o F and 1006 psig that will be resulted 4,8% CO2 of output stream.